(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The hallmark of diabetes mellitus, a chronic metabolic disease, is persistent hyperglycemia brought on by deficiencies in either insulin action or secretion, or both. The quest for alternative therapeutic agents, such as medicinal plants with hypoglycemic potential, has become necessary due to the rising prevalence of diabetes worldwide. A lesser-known medicinal plant called Mollugo nudicaulis Lam has long been utilised for a number of therapeutic purposes, such as hepatoprotective and anti-inflammatory actions. Mollugo nudicaulis Lam’s phytochemical composition, pharmacological potential, and anti-diabetic effectiveness are highlighted in this review, along with its mode of action, clinical significance, and promise for further study.